To evaluate the expression \( 6(8x - 6) + 4 \) for \( x = 8 \), we will substitute \( 8 \) in place of \( x \) and perform the calculations step by step.
-
Substitute \( x = 8 \) into the expression: \[ 6(8(8) - 6) + 4 \]
-
Calculate inside the parentheses: \[ 8(8) = 64 \ 64 - 6 = 58 \]
-
Now substitute back: \[ 6(58) + 4 \]
-
Multiply: \[ 6 \times 58 = 348 \]
-
Now add \( 4 \): \[ 348 + 4 = 352 \]
So, the evaluated expression for \( x = 8 \) is \( 352 \).
Since none of the provided options (A. 88, B. 6(8x-6)+4, C. 16, D. 46) match \( 352, \) it appears there may be a mistake in the options listed or in the interpretation of the expression to evaluate.
Thus, the expression evaluates to \( 352 \), which is not among the answer choices provided.